2008
DOI: 10.14310/horm.2002.1111033
|View full text |Cite
|
Sign up to set email alerts
|

How diet interacts with longevity genes

Abstract: In laboratory mice, suppression of growth hormone (GH) signaling by spontaneous mutations or targeted disruption of GH-or IGF1-related genes can lead to an impressive increase of longevity. Hypopituitary Ames dwarf (Prop1 df ) and GH receptor knockout (GHRKO) mice live 35-70% longer than their normal littermates. Many phenotypic characteristics of these longlived mutants resemble findings in genetically normal animals subjected to calorie restriction (CR). Microarray and RT-PCR studies of gene expression sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Our lab (this study) as well as others, have reported that Ames mice exhibit greater levels of PGC-1α mRNA in tissues as compared to control animals Bartke et al 2008). The high levels of liver PGC-1α mRNA did not result in greater mitochondrial numbers as estimated by the mitochondrial-nuclear DNA ratios.…”
Section: Discussionsupporting
confidence: 60%
“…Our lab (this study) as well as others, have reported that Ames mice exhibit greater levels of PGC-1α mRNA in tissues as compared to control animals Bartke et al 2008). The high levels of liver PGC-1α mRNA did not result in greater mitochondrial numbers as estimated by the mitochondrial-nuclear DNA ratios.…”
Section: Discussionsupporting
confidence: 60%
“…SIRT1 activators have been evaluated this way by Sirtris (Smith et al, 2009). Because some mouse models respond differently to CR, studies have focused on identifying differential responses that can be associated with the mechanisms of CR and/or used as biomarkers (Bartke et al, 2008). More recent work has also focused on identifying genes that influence the life-extending effects of CR by classic genetics using differences in lifespan in different mouse recombinant inbred strains (Liao et al, 2010).…”
Section: A Functional Genomics Of Aging and Longevitymentioning
confidence: 99%
“…Ames dwarf mice not only exhibit an increase in longevity, living 40–60% longer relative to N mice, but also an enhanced healthspan, maintaining their youthful appearance with age. These mutants show no signs of diabetes; they are extremely insulin sensitive with low levels of glucose and insulin in circulation (Brown-Borg et al ., 1996; Bartke et al ., 2001, 2008). Ames dwarf mice have improved cognitive function and show no age-related decline in memory (Kinney et al ., 2001) and are less prone to cancer (Ikeno et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that df/df mice are inclined to get obese as they age but yet maintain high adiponectin levels in circulation (Bartke et al ., 2008) and live longer and healthier lives compared with N mice leads us to hypothesize that VF in these mutants, developed in the absence of GH signaling, contributes to the enhanced insulin sensitivity of df/df mice, presumably by secreting low levels of pro-inflammatory IL-6 and increased levels of anti-inflammatory adiponectin.…”
Section: Introductionmentioning
confidence: 99%